Sensory integration of the tactile sensory system of children with developmental disabilities - Salkic, Naim; Ahmetovic, Zulfo; Velic, Safet; Prazina, Nedžad (Technium Social Sciences Journal, 2022)
Sensory integration is the organization of the senses for their use. It is a neuro-biological activity that allows the reception and processing of sensory information, which in large quantities from the senses come to the brain, at all times. The aim of the study is to examine the prevalence of sensory integration difficulties of the tactile sensory system of children with developmental disabilities, and to establish the statistical significance of differences in relation to the type of difficulty. The total sample of respondents (N=60) consisted of four subsamples of 15 respondents, namely; children with autism, children with Down syndrome, children with hearing impairment and children with sight impairment. The Mann-Whitney U test and the Wilcoxon W test at the level of statistical significance of p<0.05 were used to test the statistical significance of the differences between the subsamples of the subjects. The results of the study show that 86.67% of children with autism, 66.67% of children with Down syndrome, 20% of children with hearing impairment and 40% of children with sight impairment have difficulties with sensory integration of the tactile system. Children with hearing impairment (Rank M 43.97), children with sight impairment (Rank M 35.03), children with Down syndrome, and children with autism (Rank M 14.93) show the least difficulty in sensory integration of the tactile sensory system. There is a statistically significant difference in the difficulties of sensory integration of the tactile sensory system between children with autism, children with Down syndrome, children with hearing impairment and children with sight impairment at the level of statistical significance of p<0.05.